TikTok Shop: Unveiling the Evolution from Social Media to Social Commerce and its Computational Impact on Digital Marketing - Nur, Zinda Rud Faiza; Rabbiana, Intan Nas Nas; Diba, Tiara; Fitroh, Fitroh (ICSE (Institute of Computer Sciences and Engineering), 2023)
Social media application platforms such as TikTok have become social commerce platforms. TikTok provides the TikTok Shop feature, which is designed for business actors to make sales and users to make transactions on the TikTok application. This study used the method of studying literature from published journals available on open-source sites. It aims to present the potential of TikTok Shop as a digital marketing medium in the future. Therefore, the discussion of this literature review is only focused on the TikTok Shop feature as social commerce. TikTok Shop promoted efforts to provide improvements for MSMEs during the pandemic through an SEO marketing strategy and influencers providing interesting content according to the interests of the audience. TikTok also provides Live TikTok for business people, which is in the form of streaming video that can interact with users as potential buyers. Our research found that TikTok Shop can be one of the platforms with great potential for promoting products, supported by several TikTok Shop features for transactions.